Representação e descrição de recursos informacionais: aspectos estruturantes no delineamento de ambientes informacionais digitais - Santos, Plácida Leopoldina Ventura Amorim da Costa [UNESP]; Castro, Fabiano Ferreira de [UNESP] (My University, 2010)
The relevancy of not only the web but also the digital libraries for the diverse branches of science has stimulated researchers and scientific communities to search for integration solutions, interchange and semantic understanding about the contents that circulate in them. In this context, the proposal of this research is to verify, in the scientific literature, the applicability and functionality of the technologies and instruments available as patterns of representation and description of content and form, in the ambit of digital libraries, with the objective of identifying and characterizing the use and the application of MarcOnt as a tool for the construction of forms of information representation for digital libraries at the present time, highlighting it as an instrument for describing the semantic aspects of the digital contents in these environments. As a methodology, the present work is characterized by being an exploratory and descriptive analysis of the subject, with which it is possible to obtain subsidies for a better and more detailed understanding and comprehension of MarcOnt and the technologies that are included in the ambit of digital libraries for the semantic web construction. As a result, it was attempted to demonstrate the application of the MarcOnt tool in a specific informational environment, the JeromeDL Semantic Digital Library, to analyze the fundamentals of descriptive cataloguing the forms of representation of informational resources. Therefore, the MarcOnt semantic bibliographic description pattern offers the possibility of assuring an improvement in the interoperability performance, not only among metadata patterns, but also among digital informational systems and environments.

A relevância tanto da web quanto das bibliotecas digitais para os diversos ramos da ciência tem impulsionado pesquisadores e comunidades científicas a buscar soluções de integração, intercâmbio e entendimento semântico sobre os conteúdos que nelas circulam. Neste contexto, a proposição da pesquisa é verificar, na literatura científica, a aplicabilidade e a funcionalidade das tecnologias e dos instrumentos disponíveis como padrões de representação e descrição de conteúdo e forma, no âmbito das bibliotecas digitais. O objetivo é identificar e caracterizar o uso e a aplicação do MarcOnt como ferramenta para construção de formas de representação da informação para bibliotecas digitais, na atualidade, destacando-o como instrumento para descrição dos aspectos semânticos dos conteúdos digitais nestas ambiências. Como metodologia, caracteriza-se por ser uma pesquisa de análise exploratória e descritiva, com o qual é possível obter subsídios para maior e mais detalhado entendimento e compreensão do MarcOnt e das tecnologias abarcadas no âmbito das bibliotecas digitais para construção da web semântica. Como resultado, procurou-se demonstrar a aplicação da ferramenta MarcOnt num ambiente informacional específico, a Biblioteca Digital Semântica JeromeDL, para analisar, nos fundamentos da catalogação descritiva, as formas de representação dos recursos informacionais. Assim, o padrão de descrição bibliográfica semântica MarcOnt oferece a possibilidade de melhoria na performance de interoperabilidade, não somente entre padrões de metadados, mas também entre sistemas e ambientes informacionais digitais.
Representation and description of information resources: structural aspects in the design of digital informational environments
Keywords: MARCOnt; MARC21; Web semântica; Bibliotecas Digitais; Representação da Informação; catalogação automatizada